Ethics and morals as a panacea in school pupils’ attitude: islamic studies teachers as a model (2010)
Ethics enjoys a place of crucial importance in the structure in the structure of Islamic teaching. The negligence of moral teaching caused serious consequence of social vices that become rampant among the young ones in schools. This paper focuses on how exemplary lives of Islamic teachers can go a long way in fostering morals, characters and sound attitude of pupils, and also it gives a limelight on the role of Islamic studies teacher in the social value. Also, many Qura’nic and Prophetic injunctions would be showcased for rebreeding the moral, ethics and attitudes of the individuals in the world over especially the Islamic studies teacher.